2020
DOI: 10.21203/rs.3.rs-34879/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitudinal and demographic factors associated with seeking help and receiving antidepressant medication for symptoms of common mental disorder

Abstract: Abstract BackgroundDespite the increased attention given to improvement of mental health-related knowledge and attitudes, rates of help-seeking for mental illness remain low even in countries with well-developed mental health services. This study examines the relationships between attitudes to mental illness, symptoms of common mental disorder and seeking-help and receiving medication for a mental health problem. Methods: We used data from the nationally representative … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, the stigma-related processes that influence practices such as self-reporting may work at more interpersonal levels. For instance, one study found in the HSE that knowing someone with a mental health problem was associated with better help seeking practices [25]. Supporting this, another study also found in the HSE no variance in attitudes at the local area level (across geographical units averaging 1,500 inhabitants), but a meaningful degree of variance at the household level [26].…”
Section: Discussionmentioning
confidence: 95%
“…However, the stigma-related processes that influence practices such as self-reporting may work at more interpersonal levels. For instance, one study found in the HSE that knowing someone with a mental health problem was associated with better help seeking practices [25]. Supporting this, another study also found in the HSE no variance in attitudes at the local area level (across geographical units averaging 1,500 inhabitants), but a meaningful degree of variance at the household level [26].…”
Section: Discussionmentioning
confidence: 95%